Adaptable thermal conductive, high toughness and compliant Poly(dimethylsiloxane) elastomer composites based on interfacial coordination bonds. (5th January 2023) - Ji, Yinggang; Wen, Zhibin; Fan, Jianfeng; Zeng, Xiangliang; Zeng, Xiaoliang; Sun, Rong; Ren, Linlin
Abstract: Compliant elastomers have been widely used in industry and daily life benefited from their large reversible deformability. But poor thermal conductivity and toughness of unfilled elastomers usually limit their use in thermal management. The most common method to increase these properties is to incorporate thermally conductive fillers to polymeric materials. However, thermally conductive network formed by the large of fillers not only decreases the elastomeric compliance, but may also damages the toughness. Herein, to study the effect of polymer/filler interfacial interaction on thermal and mechanical properties, we choose shorter poly(dimethylsiloxane) without entanglement to construct elastomer composites by non-covalent interfacial carboxyl/aluminum and carboxyl/zinc oxide coordination bonds. Time-domain thermoreflectance technique demonstrates that the strong interfacial interaction leads to reduced interfacial thermal resistance between polymeric materials and fillers, resulting in enhanced thermal conductivity of the elastomer composites. Otherwise, two independent dynamic coordination bonds have been investigated on temperature- and frequency-sweep rheometer. The results reveal that the elastomer composites can counteract the negative effect of high filler content on toughness and compliance according to energy-dissipation of dissociation and generation of dynamic coordination bonds. Thanks to the enhanced interfacial interaction, our material shows high toughness (1073 J/m 2 ), thermally conductive (2.37 W/(m·K)), compliant (stress is 0.11 MPa and elongation break is 910%) and fully reprocess. For the application as thermal interface materials, we demonstrate effective heat dissipation on chip and LED. Our present work suggests that the design principles based on interfacial coordination interaction can be applied to the development of new classes of elastomer composites. Graphical abstract: Image 1